Effect of Hepatic Macrophage Polarization and Apoptosis on Liver Ischemia and Reperfusion Injury During Liver Transplantation - Ye, Liping; He, Saiqin; Mao, Xinli; Zhang, Yu; Cai, Yue; Li, Shaowei (Frontiers in Immunology, 2020)
Ischemia-reperfusion (I/R) injury is injury caused by a limited blood supply and subsequent blood supply recovery during liver transplantation. Serious ischemia-reperfusion injury is the main cause of transplant failure. Hepatic I/R is characterized by tissue hypoxia due to a limited blood supply and reperfusion inducing oxidative stress and an immune response. Studies have confirmed that Kupffer cells (KCs), resident macrophages in the liver, play a key role in aseptic inflammation induced by I/R. In liver macrophage polarization, M1 macrophages activated by interferon-γ (IFN-γ) and lipopolysaccharide (LPS) exert a pro-inflammatory effect and release a variety of inflammatory cytokines. M2 macrophages activated by IL-4 have an anti-inflammatory response. M1-type KCs are the dominant players in I/R as they secrete various pro-inflammatory cytokines that exacerbate the injury and recruit other types of immune cells via the circulation. In contrast, M2-type KCs can ameliorate I/R through unregulated anti-inflammatory factors. A new notion has been proposed that KC apoptosis may influence I/R in yet another manner as well. Management of KCs is expected to help improve I/R. This review summarizes the effects of hepatic macrophage polarization and apoptosis on liver I/R.